Teaching Media “Powtoon” to Assist Students’ Writing Narrative Text - Ai Siti Nur Fauziah; Lilies Youlia Friatin; Aa Surahmat (Jadila: Journal of Development and Innovation in Language and Literature Education, 2021)
This research explores teaching media “Powtoon” to assist students’ writing narrative text. This research aims to investigate strategies used by the teacher in using media “Powtoon” to assist students’ writing narrative text and to know how the students perceive about the use of media “Powtoon”. It was argued that the use of media “Powtoon” would provide students with powerful tool to use in the classroom. Bowman (2013) arguessthat “Powtoon offers teachers more creativity and flexibility in students instruction to help introduce, develop, and reinforce key education concept”. So, this strategy is appropriate for the teacher to invite students’ motivation and participation in learning English especially in assessing writing skill. A qualitative descriptive research was used in this research, and this research was conducted at the tenth grade of Vocational School in Karawang, and took an English teacher who teaches writing class and 18 students as samples which were chosen purposively as the sample of the study. The data were collected by using classroom observation, and interview. The result from this study showed a positive perception through strategies which were used by the teacher and help the students in improving their self confidence in practicing writing. Beside that, the students’ spelling, grammar, content and vocabulary improved because the students feel free in conveying and expressing their idea and some sentences in writing the script of the story helped them in arranging the sentences to make a good sentences. Therefore, the researcher analyzed the students’ interview. The data were displayed in four questions.The dominant answer of the students’ interview indicates that they enjoyed and motivated in following teacher’s instruction in every stages of learning process. Based on these research findings, it is recommended that the teacher can use media Powtoon in teaching writing narrative text to Vocational School students. Furthermore, this strategy was not only increasing students’ writing skill, but also increase students’ technology skill through the use of media Powtoon and classroom interaction strategies. In addition, this study also suggests that English teacher to use media Powtoon